Psychological Aspects of Training Highly Qualified Athletes in Kazakh Kuresi Wrestling - Damir A. Bekbossynov; Kulyash A. Tazabayeva; Batiyash M. Silybaeva; Beisenbek T. Akzhalov; Arai K. Amanova (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of the article is to identify the psychological aspects of the training of highly qualified athletes in Kazakh Kuresi wrestling. The leading methods for the study are the Minnesota Multiphasic Personality Inventory (MMPI) for an in-depth examination of individual characteristics of psychological functioning of personality and the diagnostic method for personal motivation to success according to the questionnaire T. Ehlers to identify the psychological skills of striving for victory in athletes. The article presents the psychological and aspects of the training of highly qualified athletes in Kazakh Kuresi wrestling. The identified aspects provide the full-fledged psychological support to highly qualified Kazakh Kuresi wrestling athletes at all levels of training and during competitions to form a correct psychological attitude with a stable individual state to many pre-competitive and competitive factors. Findings highlight the importance of comprehensive psychological support in enhancing sports performance and maintaining athletes' psychological and physical health. This research offers practical insights for high-performance sports, especially in the training of elite Kazakh Kuresi wrestlers.